Pengaruh Kualitas Pelayanan, Kemudahan Penggunaan Aplikasi Dan Harga Terhadap Loyalitas Pelanggan Pada Pengguna Aplikasi Netflix (Studi Kasus pada Mahasiswa Universitas islam Malang) - Zidan, Moh Izzad Kamal; Mardani, Ronny Malavia; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of service quality, ease of use and price on customer loyality among Netflix application users. The research employed a quantitative methode with an explanatory approach. The sampling technique used was purposive sampling, with a total of 90 respondents who are students at the Islamic University of Malang and have user or are currently using Netflix. Data were collected trough the distribution of questionnaires and analyzed using validity test, reliability test, normality test, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, t-test and the coeffisien of determination test, all processed with SPSS 30. The result of the study indicate that service quality has a significant effect on customer loyality, ease of use has a significant effect on customer loyality and price has a significant effect on customer loyality. Keywords : Customer loyality, service quality ease of use, price, Netflix